Penerapan Hukum Islam di Indonesia (Peluang Konstitusional dan Implementasinya Dalam Sistem Hukum Positif Indonesia) - Sidik Tono (Universitas Islam Indonesia, 2003)
The issue of the implementation of Islamic law is still problematic today. It locates in the tension between the Islamic political power forces and the tendencies of globalization in politics and legal system. However, it doesn't necessarily mean that the eager for the implementation of Islamic law has lost its chance. Still, there is strategic entry point for such will, i.e., through democratization process. But, again, this needs long struggle in long way of political process.